Analysis of biophysical variables in an onion crop (Allium cepa L.) with nitrogen fertilization by sentinel-2 observations - Casella, Alejandra An; Orden, Luciano; Pezzola, Nestor Alejandro; Bellaccomo, Maria Carolina; Winschel, Cristina Ines; Caballero, Gabriel; Delegido, Jesus; Navas Gracia, Luis Manuel; Verrelst, Jochem (MDPI, 2022)
The production of onions bulbs (Allium cepa L.) requires a high amount of nitrogen. Ac cording to the demand of sustainable agriculture, the information-development and communication technologies allow for improving the efficiency of nitrogen fertilization. In the south of the province of Buenos Aires, Argentina, between 8000 and 10,000 hectares per year−1 are cultivated in the districts of Villarino and Patagones. This work aimed to analyze the relationship of biophysical variables: leaf area index (LAI), canopy chlorophyll content (CCC), and canopy cover factor (fCOVER), with the nitrogen fertilization of an intermediate cycle onion crop and its effects on yield. A field trial study with different doses of granulated urea and granulated urea was carried out, where biophysical char acteristics were evaluated in the field and in Sentinel-2 satellite observations. Field data correlated well with satellite data, with an R2 of 0.91, 0.96, and 0.85 for LAI, fCOVER, and CCC, respectively. The application of nitrogen in all its doses produced significantly higher yields than the control. The LAI and CCC variables had a positive correlation with yield in the months of November and December. A significant difference was observed between U250 (62 Mg ha−1) and the other treatments. The U500 dose led to a yield increase of 27% compared to U250, while the difference between U750 and U500 was 6%.